The emerging role of epigenetics in pulmonary hypertension. Issue 3 (4th August 2016) - Gamen, Elisabetta; Seeger, Werner; Pullamsetti, Soni Savai
Epigenetics is usually defined as the study of changes in phenotype and gene expression not related to sequence alterations, but rather the chemical modifications of DNA and of its associated chromatin proteins. These modifications can be acquired de novo, being inherited, and represent the way in which genome and environment interact. Recent evidence points to the involvement of epigenetic changes in the pathogenesis of pulmonary hypertension, as they can partly explain how environmental and lifestyle factors can impose susceptibility to pulmonary hypertension and can explain the phenotypic alteration and maintenance of the disease state. In this article, we review the epigenetic regulatory mechanisms that are mediated by DNA methylation, the post-translational modifications of histone tails and noncoding RNAs in the pathogenesis of pulmonary hypertension. Furthermore, pharmacological interventions aimed at epigenetic regulators/modifiers and their outcomes in different cellular and preclinical rodent models are discussed. Lastly, the remaining challenges and future directions in which to explore epigenetic-based therapies in pulmonary hypertension are discussed. Epigenetic mechanisms and pharmacological interventions in pulmonary hypertension http://ow.ly/ykeJ3017fN8